The Dynamics of External Financing - Joakim Jansson (Uppsala University, Department of Economics, 2000)
A dynamic process underlying firms' discrete financial choices has previously been found, but without controlling for unobserved heterogeneity, this dependence can either be of a true nature or an effect of firm-specific characteristics that we cannot observe. This study extends previous research focusing on firms' discrete external financing decision by adapting a model by Honoré and Kyriazidou (2000), which accommodates both fixed effects and a lagged dependent variable, which makes it possible to establish the nature of the dependence. We find that there is a smoothing of financing, even after controlling for unobserved heterogeneity, and also that unobserved heterogeneity plays a significant explanatory role.
Keywords: C25; C32; 330; Corporate finance; Discrete choice; State dependence; Fremdkapital; Unternehmensfinanzierung; Schweden